Análisis del rol del inglés en los servicios turísticos de los guías del parque histórico. - VILLEGAS POVEDA, JUSTIN MILENA (2024)
The study focused on analyzing the role of English in the quality of tourist services provided by guides at the Historical Park. Specific objectives included describing the interaction between guides and visitors, establishing the importance of English in guiding services, and determining foreign visitors' perception of English interaction. The methodology combined qualitative and quantitative approaches through surveys directed at guides and tourists, supported by a documentary review. Results highlighted the importance of English in tourist-service provider communication and customer satisfaction. Most guides demonstrated advanced English proficiency, positively contributing to foreign visitors' experience. Tourist recommendations emphasized the importance of improving guides' communication ability and interactivity. In conclusion, the study underscored the need for effective communication and English proficiency to ensure a satisfactory tourist experience. Foreign visitors' positive perception reaffirmed English's relevance in the tourism sector, highlighting the importance of multilingual services and continuous communication skill development for guides.